From Twinkle, with love - Menon, Sandhya (New York, New York : Simon Pulse, an imprint of Simon & Schuster Children's Publishing Division, 2018)
Told through letters, aspiring filmmaker and wallflower Twinkle Mehra learns a lesson about love while directing a movie for the Midsummer Night arts festival, in which her longtime crush and his twin brother are also participating.
Twinkle Mehra has stories she wants to tell and universes she wants to explore, if only the world would listen. When fellow film geek Sahil Roy approaches her to direct a movie for the upcoming Summer Festival, it's a dream come true. And it gets her closer to her longtime crush, Neil Roy, Sahil's twin brother. Slight inconvenience: in the course of movie-making, Twinkle falls in love with adorkable Sahil.
Keywords: Dating (Social customs) -- Juvenile fiction; Brothers -- Juvenile fiction; Twins -- Juvenile fiction; East Indian Americans -- Juvenile fiction; Letters -- Juvenile fiction; High school students -- Fiction; Young adult fiction; Producers and directors -- Fiction; Dating (Social customs) -- Fiction; Brothers -- Fiction; Twins -- Fiction; East Indian Americans -- Fiction; Letters; JUVENILE FICTION -- General; East Indian Americans -- Fiction; Twins -- Fiction; Letters; Brothers -- Fiction; Dating (Social Customs) -- Fiction; Fiction; Juvenile works; Love stories; Romance fiction